z-NAF e clipping: two improvements for post-quantum hash-based digital signatures. - Zheng, Amós Yi Cong Lu (2019)
Hash-based signature schemes are a class of post-quantum algorithms that usually consist of hash-trees built upon OTS solutions. These schemes have small key sizes, eficient processing and are simple to implement, while their security properties rely basically on the pre-image or collision resistance of the their underlying hash function. Despite such advantages, however, they have relatively large signature sizes compared to traditional signature algorithms. One way of tackling this issue is to reduce the sizes of their underlying OTS algorithms. Besides that, in applications where signature verifications are done much more frequently than signature generation (e.g. trusted software distribution), it is desirable that signature verification has less overhead than signature generation. In this work, two contributions are presented to tackle these issues. The first one is a probabilistic technique that, with negligible processing overhead, allows reductions in the underlying OTS signature sizes; namely, up to 12.5% average size reduction can be achieved depending on the w parameter chosen for the signature (however, for w = 4 the reduction is only 0.2%). The second contribution is a novel OTS scheme which has all advantages of W-OTS and W-OTS+ and yet has much faster signature verification times at the cost of slightly slower signature generation times.